Pharmacokinetics of Maternal Drug Administration: Insights into Placental Transfer and Fetal Exposure - Abdullah Duhaim; Tariq Abdullah Almatroudi; Zaiad Abdullah Alghidani; Abdulsalam Saad Alhunayni; Mohamed Helmy Salama (Journal of Pharmacy and Bioallied Sciences)
Pregnancy profoundly influences the pharmacokinetics of maternally administered drugs, necessitating a comprehensive understanding of placental transfer and fetal exposure for safe and effective drug therapy. This review provides an updated overview of recent advancements in the field, comprising placental anatomy and physiology, pharmacokinetic changes during pregnancy, factors affecting placental transfer, techniques for studying transfer mechanisms, and clinical implications for maternal and fetal health. Recent discoveries explaining placental structure, function, and molecular transport mechanisms underscore the complexity of drug transfer across the placental barrier. Advances in pharmacokinetic research reveal dynamic alterations in drug absorption, distribution, metabolism, and excretion during pregnancy, which impact therapeutic drug levels and maternal-fetal outcomes. Factors influencing placental transfer, including drug properties, placental transporters, and maternal-fetal physiology, are increasingly recognized as critical determinants of fetal exposure. Innovative methodologies and technologies facilitate the study of placental drug transport, offering insights into drug-specific transfer kinetics and developmental risks.